2021
DOI: 10.1111/jocn.15749
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of the substance use and mental health characteristics of nurses who complete suicide

Abstract: Aims and objectives:To describe the substance use and mental health characteristics of nurses who complete suicide compared to non-nurses.Background: Nurses are at higher risk of suicide than the general population. The relationship between substance use, mental health and suicide in a large sample of nurses in the USA has not been previously described. Design: Retrospective observational quantitative analysis. Methods: Suicide data were retrospectively analysed in the Centers for Disease Control and Preventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 51 publications
3
33
0
Order By: Relevance
“…Pharmacists' mean age at the time of death was statistically significantly higher than the general population. This higher average age trend was also reported among nurses who died by suicide 4,7,8 and among physicians. 6 The most common means of suicide among pharmacist decedents in this study was firearms.…”
Section: Discussionsupporting
confidence: 68%
“…Pharmacists' mean age at the time of death was statistically significantly higher than the general population. This higher average age trend was also reported among nurses who died by suicide 4,7,8 and among physicians. 6 The most common means of suicide among pharmacist decedents in this study was firearms.…”
Section: Discussionsupporting
confidence: 68%
“…A recent study of nurse suicide found that nurses were significantly more likely to have positive blood toxicology results across nearly all substances than their counterparts in the general population. 5 Interestingly, in this study, nurses were not more likely to have a documented substance use disorder reported prior to death by suicide, a finding complicated by the suspicion that nurse substance use is widely underreported. 23 Factors related to this underreporting include stigma, regulatory and licensure issues, and limited access to treatment resources.…”
Section: Substance Use and Nurse Suicidementioning
confidence: 57%
“…[13][14][15] A recent study of the mental health characteristics of nurses who died by suicide found nurses being more likely than nonnurses to report a mental health problem and more likely to have a specific diagnosis of depression prior to death. 5 While not considered a mental illness per se, burnout has been reported within the nursing profession to range from 33% 16 to 50%. 17 Burnout is an emotional response to chronic job stress that involves emotional exhaustion, demoralization, cynicism, and feelings of inefficacy.…”
Section: Mental Health and Nurse Suicidementioning
confidence: 99%
See 1 more Smart Citation
“…Among the 203 nurse subjects of the study, 82% had depression, 65% had problematic substance use, and 61% had experienced job loss (Davidson et al, 2021). A similar study comparing the mental health and substance use characteristics of 2,306 nurses who died by suicide to 185,620 non-nurses who died by suicide showed statistically significant higher rates of affective disorders and substance use in nurses at the time of death, as well as job and physical health problems, indicating “mid- to long-range problems that did not develop suddenly and without warning” (Choflet et al, 2021). Bernadette Melnyk and colleagues advocate for screening programs to detect symptoms of depression in nurses, highlighting the “HEAR (Healer Education Assessment and Referral) screening program, which provides anonymous online depression screening and treatment referral .…”
mentioning
confidence: 99%